Strengthening Students’ Self-Efficacy through Scouting Extracurriculars in Primary Schools - Sriyanti Sriyanti; Ana Andriani (UM Purwokerto Press, 2025)
Self-efficacy is defined as a person's belief in assessing their own ability to carry out a task so as to achieve the goals and expected results. Self-efficacy is an individual's belief in his or her ability to complete tasks and face challenges. Strengthening self-efficacy in students is very important to form self-confidence, independence and motivation to learn. One effort that can be made to increase students' self-efficacy is through Scout extracurricular activities. This research aims to describe strengthening students' self-efficacy through scout extracurricular activities in elementary schools using the literature study method. Data was obtained from various sources, such as journals, books and articles relevant to the research topic. The results of the study show that Scout activities make a positive contribution in increasing students' self-efficacy through habituating them to discipline, independence, courage and responsibility. The learning methods applied in scouting, such as educational games, group activities, and giving awards, are able to encourage students to have more confidence in their abilities. Thus, scout extracurricular activities are an effective means of building the character and self-efficacy of students in elementary school.